Residu Urine Pasca Total Vaginal Histerektomi setelah Pemberian Misoprostol di RSUP H. Adam Malik Medan - Djaganata, Servin Pandu; Ardiansyah, Edy; Tala, M. Rhiza Z; Sihite, Herbert; Siregar, Henry Salim; Effendi, Iman Helmi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction One of the late complications of total vaginal hysterectomy (TVH) commonly involves urinary tract, i.e urinary retention (21-87%). Treatment with misoprostol can prevent the occurrence of urinary retention.Methods This study was a retrospective descriptive study using secondary data from 5-year-(January 2010-December 2014) medical records at Adam Malik Hospital in patients that underwent TVH. Samples were collected by total sampling. Data were analysed using univariate and ANOVA bivariate analysis. The p-value was considered significant if p<0.05 with a confidence interval of 95%.Results A total of 66 patients underwent TVH with mean post voiding urine volume 30.71 Â± 6.78 mL. Based on the age, one person, 6, and 59 people were alloted into the following groups: 30- 39 (1.51%), 40- 49 (9.09%), and â¥50 years old (89.39%), respectively. Each group showed no significant difference in post voiding urine volume (20 ml; 27.8 Â± 6.58 ml; 31.18 Â± 6.69 ml, sequentially). The mean residual urine obtained increased along with parity, but showed no significant difference (p> 0.05).Conclusion: In this study, urinary retention was not present in patients going for TVH treated misoprostol. There is no significant difference in mean post voiding urine volume by age and parity group.Keywords : Total Vaginal Hysterectomy (TVH); residual urine; misoprostol